Care and Love - Xiaoming, Ai (Visible Record, 2007)
Verzio FF Submission From 1995 to 1997 the Central Blood bank of Xingtai, Hebei province, China, deliberately violated state policy and transported blood out of Yuncheng, Shanxi province, to be turned into various blood products serving the markets of Beijing, Shanghai and Xingtai. Local medical suppliers in Xingtai collected blood without carrying out virus inspection, and used it during medical operations and childbirth. A decade later, many villages saw people infected with HIV and deaths from AIDS. "Care and Love" tells the story of Liu Xianhong, a Chinese villager who contracted HIV through a blood transfusion during childbirth. The film recounts how she publicized her story, filed a lawsuit with her 8-year-old son against the hospital, and eventually received compensation.